SISTEM INFORMASI TUGAS AKHIR BERBASIS WEB UNIVERSITAS SAHID SURAKARTA - Ade Setiyawan; Dwi Retnoningsih; Sri Huning Anwariningsih (JURNAL GAUNG INFORMATIKA, 2012)
Information Systems of Final Project in Sahid University of Surakarta still using manual systems, where the filing of the title is still using a paper form, the studentmust immediately meet the Study Program Chairman and academic advisor for raising titles and information about any title that has been received is still not transparent.Information about anyone who has graduated and who will graduate and the graduation schedule is not yet maximal. Information Systems of Final Project which canbe accessed quickly students are needed so that students can obtain information more quickly and accurately about the End Task. The method used in the manufacture of this Information Systems of Final Project using structured programming. Testing the system in this study using the method of Mc Call, using five factors: portability, reliability, maintainability, usability and compability. Mc Call method was chosen because it is easy to use and powerful toolto measure software quality. Information Systems of Final Project based web is the right step to provide information about the final project that can be accessed efficiently by the students who took the Final. This system can also be used as a means to consult a counselor for students enrolled following the End Task. Information Systems of Final Project which is expected to be web-based facilities that support the process of final project at the Sahid University of Surakarta. Having measured using the method of Mc Call, the total value of the quality of this system is (77,8 %)). The value of measuring the quality of the systems have been able to determine that the system can be used in Sahid University of Surakarta.